The Effect of Green Accounting, CSR Disclosure, and Profitability on Firm Value in the Consumer Non-Cyclicals Sector Listed on the Indonesia Stock Exchange 2022-2024 - Ariyanti, Ni Komang Trisna; Dewi, Kadek Goldina Puteri; Putra, Gede Sanjaya Adi (PT Keberlanjutan Strategis Indonesia, 2026)
Non-cyclical consumer companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024 will be examined for their impact on firm value, including Green Accounting, CSR Disclosure, and Profitability. Annual reports and sustainability reports from companies listed on the IDX or with official websites were used as secondary data in this research. Fifteen companies were selected as research objects after a purposive selection procedure was used to select the sample. The analytical approach used was panel data regression in EViews with additional t-tests, F-tests, and coefficient of determination (R³) analysis. Firm value was found to be simultaneously influenced by Green Accounting, CSRD, and Profitability. CSRD significantly affected firm value, while Green Accounting and Profitability only partially affected. This suggests that in the post-pandemic era, CSRD disclosure is more important to the market than environmental costs and profitability in determining firm value.